How can an association of law schools promote quality legal education? - (:unkn) unknown (My University, 2016)
The Association of American Law Schools (AALS) is the voluntary membership organization for United States law schools, with 162 member schools. The AALS attempts to accomplish its mission both by establishing and enforcing membership requirements for law schools seeking membership and by engaging in activities designed to help law teachers become better teachers and scholars.